ANALISIS LOGAM TEMBAGA (Cu) PADA BUANGAN LIMBAH TROMOL (TAILING) PERTAMBANGAN POBOYA - Nuriadi, Nuriadi; Napitupulu, Mery; Rahman, Nurdin (Jurnal Akademika Kimia, 2013)
The analyses of Copper (Cu) has been performed in the sample of drum waste (tailings) gold mining in Poboya by using Atomic Absorption Spectrophotometry (AAS) method.The alkaline destruction by the addition of HNO3 and HClO4 has been done by heating then distilled. The absorbance was measured at a wavelength (Î») = 324.7 nm on copper metal analysis. From the analysis,it was obtained copper metal in each drum consist of as follows drum A. 204.92 mg/kg, drum B 151.85 mg/kg, drum C 79.51 mg/kg, drum D 167.78 mg/kg, drum E 190.68 mg/kg, with the overall average value of 158.94 mg/kg. The data shown that the area gold mining at Poboya contain copper metal ion in high quantity.